Dispersal and population regulation of the red swamp crayfish (Procambarus clarkii) - Ramalho, Ricardo Manuel Oliveira (2012)
O objetivo principal da presente tese foi contribuir para o aumento do conhecimento acerca do lagostim-vermelho-da-Louisiana (Procambarus clarkii), uma espécie alóctone invasora na Península Ibérica. As principais conclusões da presente tese foram: · A densidade populacional teve um efeito negativo significativo sobre o crescimento de lagostins juvenis; · Foi proposto um coeficiente de aprendizagem que pode constituir uma ferramenta útil para avaliar e comparar as capacidades de aprendizagem de diferentes predadores aquáticos; · O achigã demonstrou apresentar prey-switching sobre o P. clarkii, e este facto pode ser indicador do seu potencial para regular populações de lagostim em áreas recentemente invadidas; · A densidade populacional teve um efeito significativo sobre a dispersão do P. clarkii dentro de água; · A drenagem da área de estudo constituiu um dos principais despoletadores da dispersão terrestre do lagostim. A temperatura, a humidade relativa e o período do dia foram outras variáveis ambientais que influenciaram significativamente a dispersão terrestre do P. clarkii; ABSTRACT: The main objective of the present thesis was to contribute to the improvement of the knowledge about red swamp crayfish (Procambarus clarkii), an exotic invasive species in Iberian Peninsula. The main conclusions of this thesis were: · Population density had a significant negative effect on juvenile crayfish growth; · A learning coefficient was determined that can provide an useful tool to evaluate and compare the learning capabilities of different freshwater predators; · M. salmoides revealed prey switching towards P. clarkii and this may be an indication of its potential for population regulation in crayfish recently invaded areas; · Population density significantly affected underwater P. clarkii dispersal. Other factors involved were the water temperature and period of the day; · One of the main factors inducing P. clarkii overland dispersal was the drainage of the study area. Other variables that significantly influenced the overland dispersal of P. clarkii were the temperature, relative humidity and the period of the day.